2006
DOI: 10.1021/cm061656f
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of Mg Insertion into Chevrel Phases, MgxMo6T8 (T = S, Se). 1. Crystal Structure of the Sulfides

Abstract: A combination of ab initio calculations and experimental methods (high-resolution neutron and powder X-ray diffractions) was used to solve the crystal structure of Mg x Mo6S8 (x = 1 and 2). It was shown that at room temperature, the latter are similar to the crystal structure of classic Chevrel phases (CPs) such as Cu x Mo6S8:  space group R3̄, a r = 6.494 Å, α = 93.43° for MgMo6S8 and a r = 6.615 Å, α = 95.16° for Mg2Mo6S8. For x = 1, one Mg2+ cation per formula unit is distributed statistically between inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(192 citation statements)
references
References 44 publications
8
184
0
Order By: Relevance
“…This charge trapping is attributed to circular motion of Mg 2+ in the inner ring, since Mo-Mg interactions create a large energy barrier to escape the low-potential inner ring sites [117]. Levi et al [138] found that the improved mobility of Mg during the second reaction is a consequence of increased repulsion between Mg 2+ ions. Apart from the charge trapping, the high mobility is related to the nature of CPs, where the 3D channels of closely spaced vacant sites prevent Mg 2+ ions from occupying adjacent sites.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…This charge trapping is attributed to circular motion of Mg 2+ in the inner ring, since Mo-Mg interactions create a large energy barrier to escape the low-potential inner ring sites [117]. Levi et al [138] found that the improved mobility of Mg during the second reaction is a consequence of increased repulsion between Mg 2+ ions. Apart from the charge trapping, the high mobility is related to the nature of CPs, where the 3D channels of closely spaced vacant sites prevent Mg 2+ ions from occupying adjacent sites.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Therefore, the two reactions exhibit different activation-energy barriers. 28,29 The characteristic structure of Mg 2 Mo 6 S 8 also appears to affect the ion mobility in the solid. In 2005, Levi et al used the classical potentiostatic intermittent titration technique (PITT) to measure the solid diffusivity of Mg x Mo 6 S 8 as a function of Mg content, x.…”
Section: Rate Behavior Of Chevrel Phasementioning
confidence: 99%
“…Levi et al measured D s,fast using the PITT method; however, as mentioned above, they could not measure the lower diffusivity, D s,slow , because the value was too small, caused by Mg ions trapping. 28,29,38 For the exchangecurrent density, i 0 , no reported value of Mg x Mo 6 S 8 in APC/THF (Eq. 4) was found in the literature; therefore, we used i 0,fast , i 0,slow , and D s,slow as fitting parameters in the model.…”
Section: Mathematical Model Assumptions and Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Downloaded on 2018-05-12 to IP anisotropic channel character, would not allow filling of a larger part of the vacant sites although the number of them is high in o-Mo 9 Se 11 . 21 On the other hand, in the case of Chevrel compounds, Mo 6 X 8 (X = S, Se), with three-dimensional diffusion channel, 33 it is reported that both Li-and Mg-systems show the similar order capacity comparable with the theoretical capacity 11,12,[17][18][19][20]34,35 deduced from the molecular orbital model, 23 in which extra four electrons per formula unit form closed-shell configuration of bonding orbitals. The threedimensional diffusion channel could work effectively to reduce the energy increase by Coulomb repulsion between the inserted ions.…”
Section: Resultsmentioning
confidence: 72%